Perfil e atuação dos profissionais de apoio à inclusão escolar - Lopes, Mariana Moraes (2018)
School Inclusion has grown every year, and with the increased enrolment of students with disabilities in regular schools, the demand for stronger support networks and differential care has grown. In this scenario a new character has gained prominence, and although they have received many different denominations, such as "attendant", "caregiver", "trainee", "auxiliary", "escort" etc.; here they will be called School Inclusion Support Professional (SISP). Still lacking in function and well-defined assignments, with no specific professional profile and unknown working conditions, the figure of these SISP, although relatively recent in schooling policies, has become increasingly frequent and conflicting in school contexts. Considering that this character can be an important support to allow the process of school inclusion of students that require this type of support, but that can also be used as a mechanism of cheapening and simplification of the support system, the present study aimed to describe and analyse the profile and performance of SISP in different municipal contexts. This descriptive study carried out in five municipalities, three in the state of Bahia and two in the state of São Paulo, involved procedures based on individual interviews and focus groups. In total, 35 support professionals participated, ranging from five to seven per city, in addition to five representatives from the Education Department, one from each city. The design of the study involved three stages, namely: I) Elaboration of instruments in the form of interview scripts for focus groups; II) Execution of focal group I - with support professionals of each city; III) Semi-structured interview with a Special Education representative of the municipalities. Data analysis involved the transcription of the interviews and data processing through Atlas-Ti®. The results evidenced the importance of SISP in the school context, but at the same time a precarious and worrisome scenario of how this type of support has been used by school inclusion policies. Hopefully, the present study has contributed to the academic area to reflect on school inclusion support policies, considering the novelty of the theme and the still scarce scientific evidence, as well as the educational system, by pointing out the need to define guidelines that regulate the variety of profiles, attributions, working conditions and courses of action found in the different realities of SISP